Aspectos da linguagem e do espetáculo cinematográficos na narrativa literária brasileira do século XX - Rodrigues, Ana Paula Dias [UNESP] (2014)
The attention to the relation between literature and cinema occupied the literary criticism since the invention and popularization of the cinematographic art in the twentieth century. Some of the pessimistic predictions pointed to the death of the genres, of the book and even of the literature. In the field of literary production, however, it is possible to observe different reactions of literature face to the cinematographic language and spectacle that show since a deliberate adhesion to new cinematographic effects, procedures and means to a definitive refuse to the aesthetic and ethic means of cinema. This work presents a reflexion about the aspects of the cinematographic language and spectacle's manifestation in the canonical and non-canonical literary works of twentieth century Brazilian literary narrative. The investigative way initiates in Pathé-Baby (1926), by António de Alcântara Machado, goes to Vidas Secas (1938), by Graciliano Ramos, passes to Cara-de-bronze (1956), by Guimarães Rosa and ends in Maciste no inferno (1982), by Valêncio Xavier